2015
DOI: 10.5194/acp-15-2215-2015
|View full text |Cite
|
Sign up to set email alerts
|

A negative feedback between anthropogenic ozone pollution and enhanced ocean emissions of iodine

Abstract: Abstract. Naturally emitted from the oceans, iodine compounds efficiently destroy atmospheric ozone and reduce its positive radiative forcing effects in the troposphere. Emissions of inorganic iodine have been experimentally shown to depend on the deposition to the oceans of tropospheric ozone, whose concentrations have significantly increased since 1850 as a result of human activities. A chemistry-climate model is used herein to quantify the current ocean emissions of inorganic iodine and assess the impact th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 30 publications
(41 reference statements)
2
68
1
Order By: Relevance
“…15. The marine boundary layer O x loss attributable to halogens is comparable to the 31 % reported by Prados-Roman et al (2015a) previously, and it is higher than the 26 % reported solely for iodine (Sherwen et al, 2016a). The inter-reaction of halogen monoxide species is found to less important here than previous studies (e.g.…”
Section: Ozonecontrasting
confidence: 47%
“…15. The marine boundary layer O x loss attributable to halogens is comparable to the 31 % reported by Prados-Roman et al (2015a) previously, and it is higher than the 26 % reported solely for iodine (Sherwen et al, 2016a). The inter-reaction of halogen monoxide species is found to less important here than previous studies (e.g.…”
Section: Ozonecontrasting
confidence: 47%
“…Over the subtropics, IO enhancements observed below 4 km are not captured by the model. Some studies suggest that there is abiotic CH 3 I production when dust contacts seawater containing iodide (Williams et al, 2007;Puentedura et al, 2012). Implementing this chemistry into the model is out of the scope of this paper and further investigation is needed to explain whether the production of CH 3 I enhances the IO concentration or if there are other missing IO precursors.…”
Section: Gas-phase and Heterogeneous Chemistry: Brominementioning
confidence: 99%
“…Recent laboratory experiments and modeling predictions have suggested that abiotic precursors would contribute to the majority of the observed global iodine oxide (IO) budget [Carpenter et al, 2013;Prados-Roman et al, 2015] (typical daytime MBL levels are~1 pptv), one of the main iodine oxidized compounds leading to particulate iodine. In addition to potential ocean abiotic iodine sources, we further show that among all biological parameters monitored in the seawater during the experiment (see supporting information), a significant correlation was found in the control mesocosm between iodine-containing species concentrations and some phytoplanktonic pigments (peridinin, chlorophyll b, and zeaxanthin) but not with the total autotrophic biomass (Chl a) (Figure 3b).…”
Section: Relationships To the Biochemical Composition Of The Seawatermentioning
confidence: 99%